The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0103-50532008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis (CE): a powerful tool to characterize humic acid (HA)

Abstract: Neste estudo, avaliou-se a possibilidade de eliminação das etapas de purificação envolvidas na caracterização de HA. HA de diferentes fontes foram analisados por CZE apresentando diferentes eletroferogramas. Essas diferenças observadas mostram que a caracterização do HA por CZE depende da carga e do tamanho do HA. Os resultados apresentados neste trabalho sugerem que não é necessária a purificação da amostra para a caracterização de HA por CZE. Baseados nos resultados, a CZE mostrou-se uma ferramenta promissor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Capillary electrophoresis (CE) has become an attractive method for acquiring a "finger-print" characterization of humic acids (de Moraes and Rezende, 2008;Garcia-Perez et al, 2008). Pompe et al (1996) reported the characteristic capillary electropherograms of five humic acids and two fulvic acids of commerical origin.…”
Section: Introductionmentioning
confidence: 99%
“…Capillary electrophoresis (CE) has become an attractive method for acquiring a "finger-print" characterization of humic acids (de Moraes and Rezende, 2008;Garcia-Perez et al, 2008). Pompe et al (1996) reported the characteristic capillary electropherograms of five humic acids and two fulvic acids of commerical origin.…”
Section: Introductionmentioning
confidence: 99%
“…There are three primary types of humic compounds: humic acid (HA), fulvic acid, and humin. Humic acid, in particular, is a valuable substance characterized by numerous functional groups along its chain (Moraes and Rezende, 2008). Humic acid comprises approximately 51% to 57% carbon (C), 4% to 6% nitrogen (N), 0.2% to 1% phosphorus (P), and trace amounts of other elements.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional MSP, the improved approach can amplify multiple regions of the template in one reaction tube with several pairs of primers, thus saving a large amount of time, labor, and template for the experiment. Furthermore, multiplex PCR products detection is coupled with capillary electrophoresis (CE), which has become an attractive separation method because of its excellent advantages including fast‐separation, high‐resolution, and less sample consumption, thus giving rise to notable savings of labor and reagent costs, and errors from sample pretreatment steps can also be avoided . Thus, this study aimed to provide a more sensitive and efficient detection method for screening and making prognosis prediction for liver cancer.…”
Section: Introductionmentioning
confidence: 99%